Akermanite reinforced PHBV scaffolds manufactured using selective laser sintering. Issue 8 (22nd March 2019) - Diermann, Sven H.; Lu, Mingyuan; Dargusch, Matthew; Grøndahl, Lisbeth; Huang, Han
Abstract: Scaffold assisted tissue engineering presents a promising approach to repair diseased and fractured bone. For successful bone repair, scaffolds need to be made of biomaterials that degrade with time and promote osteogenesis. Compared to the commonly used ß‐tricalcium phosphate scaffolds, Akermanite (AKM) scaffolds were found to degrade faster and promote more osteogenesis. The objective of this study is to synthesize AKM micro and nanoparticle reinforced poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate; PHBV) composite scaffolds using selective laser sintering (SLS). The synthesized composite scaffolds had an interconnected porous microstructure (61–64% relative porosity), large specific surface areas (31.1–64.2 mm −1 ) and pore sizes ranging from 303 to 366 and 279 to 357 μm in the normal and lateral direction, respectively, which are suitable for bone tissue repair. The observed hydrophilic nature of the scaffolds and the swift water uptake was due to the introduction of numerous carboxylic acid groups on the scaffold surface after SLS, circumventing the need for postprocessing. For the composite scaffolds, large amounts of AKM particles were exposed on the skeleton surface, which is a requirement for cell attachment. In addition, the particles embedded inside the skeleton helped to significantly reinforce the scaffold structure. The compressive strength and modulus of the composite scaffolds were up to 7.4 and 103 MPa, respectively, which are 149 and 197% of that of the pure PHBV scaffolds. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B:2596–2610, 2019.